EFFECT OF ADDITION OF SESAME OIL TO DIETS ON BLOOD LIPID PROFILE OF LAYING HENS - AL-Fadhli, Murad K.; Theabe, Ammar T.; Razook, Raad H. (Diyala Agricultural Sciences Journal, 2015)
This experiment was carried out at the poultry farm of Animal Resources Dept. / College of Agriculture / University of Baghdad during the period from 22/ 10/2012 to 22/ 4/2013 to investigate the effect of adding different levels of sesame oils to layer hens diets on some biochemical trails of blood serum. Sixty four Lohmann Brown laying hens at 20 weeks age were used in this experiment. At 22 weeks of age، the hens were individually weighed and randomly distributed into four treatments and each treatment with two replicates (8 hens / replicate). The treatments were as follows: T1 (control) no addition. T2، T3 and T4 included addition of 0.5، 0.75 and 1% sesame oil respectively. The results revealed that the treatments included the addition of sesame oil were significantly lowered the levels of total blood serum cholesterol ، blood serum triglycerides compared with control ، and the treatments achieve the lower low density lipoprotein (LDL)، but significant increased in the level of high density lipoprotein (HDL).